Pan-Islamism: Ideas and Their Influence on Education in West Java - Eky Diaz Nurul Agustina; Shabri Sentosa; Umaya Resa Wijayanti (Adabuna)
Pan-Islamism is an ideological movement that emerged as a reaction to colonialism, political fragmentation, and modernization, with the aim of uniting Muslims throughout the world. In the 20th century, Pan-Islamism exerted a significant influence in West Java, particularly through the dissemination of Pan-Islamic values through Islamic boarding schools and madrasahs. This study aims to understand how the ideology of pan-Islamism has been integrated into the education system in West Java and its impact on the formation of religious and social identity of the Muslim community. By using a qualitative approach method through library research, looking for answers in various documents, articles, related literature. As a result, it has been concluded that the ideology of pan-Islamism has provided an impetus for the renewal of the Islamic education system in West Java, that the ideology of pan-Islamism not only expands their curriculum, but also gives rise to global unity of Muslims, strengthens the position of the Muslim network, and renews teaching methods. Pesantren such as Persis are real examples of how pan-Islamist principles can be applied in education to produce a generation of Muslims who are knowledgeable in religion and common sense. This study enhances the understanding of how Pan-Islamism influences West Javanese education and encourages Muslims there to unite. These findings are very important for further research on how educational reform and religious ideology correlate in the history of Indonesian Islam.